2015
DOI: 10.1371/journal.ppat.1004988
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 Down-Regulates the Insulin-Like Growth Factor Binding Protein 2 to Promote Epithelial Invasion in Organotypic Cultures

Abstract: Cervical cancer is a multi-stage disease caused by human papillomaviruses (HPV) infection of cervical epithelial cells, but the mechanisms regulating disease progression are not clearly defined. Using 3-dimensional organotypic cultures, we demonstrate that HPV16 E6 and E7 proteins alter the secretome of primary human keratinocytes resulting in local epithelial invasion. Mechanistically, absence of the IGF-binding protein 2 (IGFBP2) caused increases in IGFI/II signalling and through crosstalk with KGF/FGFR2b/AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…At least two nonexclusive hypotheses could explain this paracrine effect. First, the HPV oncogenes might alter the epithelial secretion repertoire in vivo as they do in keratinocytes cultured in organotypic rafts (44), leading to stromal changes. Second, changes in the number and/or content of extracellular vesicles secreted by HPV + epithelial cells and delivered to stromal cells might alter stromal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…At least two nonexclusive hypotheses could explain this paracrine effect. First, the HPV oncogenes might alter the epithelial secretion repertoire in vivo as they do in keratinocytes cultured in organotypic rafts (44), leading to stromal changes. Second, changes in the number and/or content of extracellular vesicles secreted by HPV + epithelial cells and delivered to stromal cells might alter stromal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in complete media (Dulbecco's modified Eagle's medium: Nutrient Mixture F-12 containing 4500 mg/L glucose, L-glutamine, and sodium bicarbonate, supplemented with 10% foetal calf serum) at 37 o C, in 5% CO2. Immortalized lines were generated by retroviral expression of mTERT 38 (iTTF), similarly to generate BiP overexpressing cells were we utilised pCMMP-BiP-IRES-mRFP a gift from Bill Sugden (Addgene plasmid #36975) 39 , using methods previously described 40 . BiP overexpressing cells were flow sorted based on mRFP expression.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…In addition, E7 interacts directly with IGFBP3 and inhibits apoptosis mediated by this protein [38]. It has also shown that in 85% of women with HSIL, IGFBP 2 loss expression occurs, which could has clinical utility for monitoring patients with a higher risk of CxCa progression [39]. Some epigenetic mechanisms have been described in CxCa, related to the effects of HPV on viral and host genome [40,41].…”
Section: Contribution Of Insulin Resistance To Cxca Riskmentioning
confidence: 99%
“…Some of them involve the components of the IGF system, such as IGF2 loss of imprinting, which can lead to some genes overexpression and overall chromatin instability [42] and E7 interaction with a group of lncRNA that modulate PI3K/Akt/mTOR and Wnt- catenin pathways in cervical carcinogenesis process [43]. It is expected that epigenetic factors that are induced by HPV or triggered in response to viral infection/viral protein expression could be important drug targets for viral associated cancers [39]. The reversibility of epigenetic modi ications makes such factors ideal therapeutic targets.…”
Section: Contribution Of Insulin Resistance To Cxca Riskmentioning
confidence: 99%